ANALYSIS QUALITATIVE ADDITION OF ADDITIVE SUBSTANCE TO PAPER MAKING PROCESS IN PAPER MACHINE 12 PT. X - KARAWANG ON PRODUCT QUALITY - Dian Farkhatus Solikha (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2020)
Paper is a tangible item of thin sheets which can be torn, rolled, folded, glued and crossed out. Paper is made to meet the needs of a very diverse life. The paper industry is one of the forest products industries which has a very important role in human life. There is almost no human activity that does not utilize this industrial commodity. In the process of making paper, in addition to the availability of Raw Materials there is also the use of additives. Additives are ingredients that are added to obtain certain desired characteristics of paper products. Some factors that influence the process of making paper are raw material, machine cleanliness, machine performance, human factors and additives. Additives are the main factors that influence the success of the papermaking process. There are two types of additives used in Paper Machine 12 PT.X-Karawang, namely functional additives and controlling additives. The effect of the addition of additives on Paper Machine 12 PT.X-Karawang namely, Dry Strength can increase the strength of the paper when used in dry conditions, Sizing Agent (Internal Sizing) functions to control liquid penetration, Surface Sizing Agent (Surface Sizing) functions to level the surface of the paper, Filler as filler, Dyes can give color to paper, OBA serves to increase the brightness of paper, Biocide functions to inhibit bacterial growth, Defoamer functions to prevent foam formation and Retention Aid can increase fiber retention.Keyword: Controlling Additives, Functional Additives, Paper, Paper Machine